PENENTU KEPUASAN PELANGGAN & IMPLIKASINYA PADA LOYALITAS PELANGGAN - Della Maretha; Muhammad Halilintar; Septian Yudi Anggara (Jurnal Manajemen FE-UB, 2023)
This study aims to determine the extent to which service quality and product quality influence customer satisfaction and the implications for customer loyalty at Happytooth Family Dental Care. The data used in this research is in the form of primary data collected from the answers of respondents based on the questionnaires given, namely as many as 198 people. The data processing method uses the path analysis method (Path Analysis) with the help of SPSS version 22.0. Statistical testing using individual parameter significance test (t test) and simultaneous significance test (F test) and Sobel test. The results showed that service quality has a positive and significant effect directly or indirectly through patient satisfaction on customer loyalty, product has a positive and significant effect directly or indirectly through patient satisfaction on customer loyalty and customer loyalty has a direct positive effect on customer loyalty Keywords: service quality, product quality, customer satisfaction and customer loyalty